What's Up Doc? Seventh Sons in Victorian and Edwardian Lancashire. Issue 4 (2nd October 2019) - Young, Simon
Abstract: Folklorists have long acknowledged that seventh sons had a reputation as healers in England. It has not previously been appreciated that in the region around Blackburn, Lancashire, seventh sons were frequently given the Christian name 'Doctor' in Victorian and Edwardian times. This article examines seventh-son traditions there and their connection to healing by reconstituting families with sons named 'Doctor'. The article finishes with two reflections on folklore transmission and folk beliefs in Lancashire in the nineteenth and early twentieth century.